Patient experience: determinants and manifestations. Issue 2 (22nd May 2019) - Zakkar, Moutasem
Abstract : Purpose: Patient experience is a complex multidimensional phenomenon that has been linked to constructs that are also complex to conceptualize, such as patient-centeredness, patient expectations and patient satisfaction. The purpose of this paper is to shed light on the different dimensions of patient experience, including those that receive inadequate attention from policymakers such as the patient's lived experience of illness and the impact of healthcare politics. The paper proposes a simple classification for these dimensions, which differentiates between two types of dimensions: the determinants and the manifestations of patient experience. Design/methodology/approach: This paper uses a narrative review of the literature to explore select constructs and initiatives developed for theorizing or operationalizing patient experience. Literature topics reviewed include healthcare quality, medical anthropology, health policy, healthcare system and public health. Findings: The paper identifies five determinants for patient experience: the experience of illness, patient's subjective influences, quality of healthcare services, health system responsiveness and the politics of healthcare. The paper identifies two manifestations of patient experience: patient satisfaction and patient engagement. Originality/value: The paper proposes a classification scheme of the dimensions of patient experience and a concept map that links together heterogeneous constructs related to patient experience. The proposed classification and the concept map provide a holistic view of patient experience and help healthcare providers, quality managers and policymakers organize and focus their healthcare quality improvement endeavors on specific dimensions of patient experience while taking into consideration the other dimensions.